Amount of Rework Minimization on Warehouse Construction Project by System Dynamics Implementation - Susanto Firdaos, Albert Eddy Husin, Mohamad Imam Suradi Fadilah, Michael Kelvin Eddy Husin (International Journal of Advanced Science and Technology, 2020)
The cost of reworking on warehouse and industrial building construction works ranges from 2.4% to 12.4% of the total construction costs. Researchers chose the Dynamic System approach to reduce the cost of rework in warehouse construction work, because the causes of rework that are always changing with time such as rain which characteristics can change every time. The results of the case study analysis of the warehouse construction project with the application of a dynamic system, obtained the efficiency of rework costs from 3 scenarios, namely 11.93%, 10.48% and 12.02% of the total cost of the warehouse construction project. Keywords: Rework, Systems Dynamic, Warehouse Construction, Cost Efficiency